Dental Management of a Patient with Pulmonary Atresia and Ventricular Septal Defect - Ghassem Ansari; Mahsa Mansouri; Leila Eftekhar (Tehran University of Medical Sciences, 2021)
Pulmonary atresia with ventricular septal defect (PA/VSD) is one of the congenital heart diseases that results in cyanosis, susceptibility to bacterial endocarditis, and increased risk of complications during general anesthesia. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common inherited genetic disorder affecting the red blood cells. We aimed to elaborate the potential dental management for patients with this serious condition. This report presents the single-visit dental treatment of a three-year-old female with PA/VSD, G6PD deficiency and rampant caries. The complexity of dental treatments, high incidence of dental caries, lack of cooperation, and the systemic condition limit treatment options to providing service under general anesthesia and hospitalization. Careful monitoring of oxygen saturation during general anesthesia and antibiotic prophylaxis are essential due to the invasive nature of dental treatments. It appears that single-visit dental management under general anesthesia minimizes the risk of treatment of patients at high risk of bacterial endocarditis.